Safety and effectiveness of coronary intravascular lithotripsy for treatment of severely calcified coronary stenoses: the Disrupt CAD II study - Ali, Z; Nef, H; Escaned, J; Werner, N; Banning, A; Hill, J; De Bruyne, B; Montorfano, M; Lefevre, T; Stone, G; Crowley, A; Matsumura, M; et al. (American Heart Association, 2019)
BACKGROUND: The feasibility of intravascular lithotripsy (IVL) for modification of severe coronary artery calcification (CAC) was demonstrated in the Disrupt CAD I study (Disrupt Coronary Artery Disease). We next sought to confirm the safety and effectiveness of IVL for these lesions. METHODS: The Disrupt CAD II study was a prospective multicenter, single-arm post-approval study conducted at 15 hospitals in 9 countries. Patients with severe CAC with a clinical indication for revascularization underwent vessel preparation for stent implantation with IVL. The primary end point was in-hospital major adverse cardiac events (cardiac death, myocardial infarction, or target vessel revascularization). An optical coherence tomography substudy was performed to evaluate the mechanism of action of IVL, quantifying CAC characteristics and calcium plaque fracture. Independent core laboratories adjudicated angiography and optical coherence tomography, and an independent clinical events committee adjudicated major adverse cardiac events. RESULTS: Between May 2018 and March 2019, 120 patients were enrolled. Severe CAC was present in 94.2% of lesions. Successful delivery and use of the IVL catheter was achieved in all patients. The post-IVL angiographic acute luminal gain was 0.83±0.47 mm, and residual stenosis was 32.7±10.4%, which further decreased to 7.8±7.1% after drug-eluting stent implantation. The primary end point occurred in 5.8% of patients, consisting of 7 non-Q-wave myocardial infarctions. There was no procedural abrupt closure, slow or no reflow, or perforations. In 47 patients with post-percutaneous coronary intervention optical coherence tomography, calcium fracture was identified in 78.7% of lesions with 3.4±2.6 fractures per lesion, measuring 5.5±5.0 mm in length. CONCLUSIONS: In patients with severe CAC who require coronary revascularization, IVL was safely performed with high procedural success and minimal complications and resulted in substantial calcific plaque fracture in most lesions. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT03328949.